Development Strategy of New-Energy Aero-engines - Zeyong Yin; Jianrong Li; Yaxin Qin; Wei Li; Shuiting Ding; Xiao Yu; Xianglei Liu; Min Li; Ming Li; Xiangyu Wang (中国工程科学)
The progress of replacing coal, oil, and other fossil energies with new energy sources is accelerating worldwide. New energy sources and associated power systems are reconfiguring the world’s development pattern. Therefore, it is necessary to accelerate the transformation from traditional fossil-fuel to new-energy aero-engines, thus to achieve carbon peaking and carbon neutrality goals and ensure aviation energy security and sustainable development of the aviation industry. This study summarizes the development values of various new-energy aviation power, including solar, electric, hydrogen, nuclear, and ammonia energy, as well as sustainable aviation fuels. It also analyzes the trends in integration of new energies with aviation power, and explores the engineering practicability and application scenarios of transformation from new energy sources to aviation power. Moreover, the development goals and priorities are proposed: promoting the coordinated development of sustainable aviation fuels and independent aero-engine products, strengthening research on electric and hydrogen aviation power technologies, promoting the application of solar aviation power, and exploring nuclear aviation power. The following development suggestions are further proposed: (1) establishing a special project for the coordinated development of new energy and aviation technologies and industries, (2) accelerating the research and application of new-energy aero-engines, (3) strengthening financial and fiscal support for the new-energy aero-engine industry, and (4) building an international cooperation ecosystem for new-energy aero-engines. These suggestions aim to comprehensively enhance the technological innovation capability and core competitiveness of the aviation industry, support the upgrading of advanced aviation equipment, and promote the continuous optimization of the industry.